Effects of predamage and load cyclic on compression behavior of fiber reinforced polymer‐confined concrete. (21st January 2021) - Cao, Yu‐Gui; Hou, Can; Liu, Mu‐Yu; Jiang, Cheng
Abstract: Most existing studies on fiber reinforced polymer (FRP) confined concrete have focused on undamaged concrete that is subjected to uniaxial monotonic compression. However, FRP jackets are usually applied to concrete columns with existing material damage and potential future damage. This paper investigates FRP confinement on concrete with damage before and after FRP jacketing. A total of 32 FRP‐confined concrete specimens were tested under axial compression in this work. The prior damage before FRP jacketing was implemented as predamaging by applying preloading and then release on the plain concrete specimens. The post damage after FRP jacketing was performed by applying cyclic axial compression loading on FRP‐confined concrete specimens. The test results reveal that the concrete predamage levels have significant influences on the cyclic stress–strain curve and envelop stress–strain curve for FRP confined concrete under cyclic loading. Existing models on ultimate state, plastic strain, reloading and unloading moduli were evaluated and investigated in this work.